ANTONYMIC RELATIONS IN THE SEMANTIC FIELD OF “HEAD”: ANALYSIS IN ENGLISH AND UZBEK (The Conference Hub, 2025)
This article aims to explore antonymic relations in idioms involving the word head in English and bosh in Uzbek. Through comparison of idiomatic pairs that reflect oppositional meanings (e.g., pride vs. shame, control vs. chaos), both parallel conceptual metaphors and culturally distinct expressions have been identified throughout the study. Figurative expressions embody the unique cultural perspectives of each language. Although they also often arise from universal human experiences. To understand this interplay between the universal and the culture-specific is essential for grasping the deeper meaning of idioms and to enhance both effective translation and language teaching practices.